Current state of formation of local public administration and self-government - Kemel , M. (BUKETOV BUSINESS REVIEW, 2017)
The article describes the main directions for further improvement of local self-government in the control system of Kazakhstan: a) the involvement of rural residents in the decision-making at the local level, including their implementation; b) build the basic principles of organization and activity of local self-government; с) providing more specific legislative norms of the organization meeting and gatherings of the local community, in particular the introduction of a rule to provide the local population the right to participate in monitoring the use of budget funds allocated for the solution of problems of local importance; g) inclusion in existing programs development district (city of regional significance) as well as regions, formed in large cities, which will be reflected priority needs of the population, taken at the meetings of the local community at the village level, rural district, town, city of district significance; d) the order of formation of functions of local authorities, increase their financial autonomy. To bring to logical completion of decentralization between levels of government were determined the basic principles of organization and activities of local governments that each level of management to consolidate the functions and responsibilities for each of them. In the modern world the welfare of the state determined by the effective use of the potential of the nation in General and the abilities of individual citizens. Specific proposed consolidation of legislation regulating the order of formation, conducting and powers of the Assembly and meetings, and identification of specific issues of funding of local importance.